SOX3 duplication in a boy with 46,XX ovotesticular disorder of sex development and his 46,XX sister with atypical genitalia: Probable germline mosaicism - Oliveira, Flávia Marcorin; Barros, Beatriz Amstalden; Santos, Ana Paula; Campos, Nilma Lúcia Viguetti; Mazzola, Taís Nitsch; Filho, Paulo Latuf; Andrade, Liliana Aparecida Lucci De Angelo; Guaragna, Mara Sanches; Mello, Maricilda Palandi; Guerra‐Junior, Gil; Vieira, Társis Antonio Paiva; Maciel‐Guerra, Andréa Trevas (American journal of medical genetics. Part A, 2023)
Ovotesticular disorders of sex development (OT‐DSD) are characterized by ovarian follicles and seminiferous tubules in the same individual, with a wide range of atypical genitalia. We report on two sibs with atypical genitalia and SRY‐negative 46,XX DSD, OT‐DSD was confirmed only in the boy, while the girl had bilateral ovaries. Chromosome microarray analysis (CMA) showed a 737‐kb duplication at Xq27.1 including the entire SOX3 gene in both sibs, which was confirmed by quantitative real time PCR. Also, X chromosome inactivation assay showed random inactivation in both sibs. Whole exome sequencing revealed no pathogenic or likely pathogenic variant. CMA of the parents showed normal results for both, suggesting that germline mosaicism could be the reason of recurrence of this duplication in the siblings. Our results support a pathogenic role of SOX3 overexpression in 46,XX subjects leading to variable DSD phenotypes.